Complications and Immediate Outcome of Pregnant Diabetic Women (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Aim: To see complications and immediate outcome among pregnant diabetic women. Methods: This observational retrospective study included sixty nine pregnant women with diabetes (both pregestational and gestational diabetes) those who got admitted and treated at Dhaka Medical College Hospital (DMCH), Dhaka Bangladesh from the 1st August 2007 to the 31st August 2008. Detailed analysis of their obstetric history, ante partum and intra partum complications and mode of delivery were performed. Results: Majority of the women (76.92%) were admitted through labor emergency. Mean age of the women was 28.9 (18-45) years. Fifty four (54%) percent of women belonged to 21-30 years age group. Sixty two (62.31%) percent of women had gestational diabetes whereas 37.68% had pregestational diabetes. All women were followed up both by obstetrician and diabetologist. Twenty five percent(25%) women developed pre-eclampsia and pregnancy induced hypertension, thirteen percent(13% )women developed premature ruptur of fetal membrane(PROM), twenty three percent (23.25% )women had fetal distress, three(2.88%) percent women present with ante-partum hemorrhage(APH) and one percent(1.44%) women develop acute polyhydromnios. Average gestational age was 36.83(41-28) weeks. Sixty percent (60%) delivered after 37weeks of gestation and forty one (40.58%) delivered before 37weeks of gestation. Ten percent women delivered vaginally and ninety percent (90%) women delivered by caesarean section (CS) because of post CS, repeat CS, breech presentation, preeclampsia, fetal distress and obstructed labor. Maternal mortality is 1.44% and peri-natal is mortality 8.62%. Conclusion: Ante-partum and intra-partum complications are more common among pregnant diabetic women. Knowledge of the importance of maternal glycemic control, as well as development of surveillance techniques to prevent complications, resulted in a decline in fetal and neonatal mortality. DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11361 J Bangladesh Coll Phys Surg 2012; 30: 10-16